2021
DOI: 10.1016/j.irfa.2020.101646
|View full text |Cite
|
Sign up to set email alerts
|

Return connectedness across asset classes around the COVID-19 outbreak

Abstract: In this paper, we show evidence of a dramatic change in the structure and time-varying patterns of return connectedness across various assets (gold, crude oil, world equities, currencies, and bonds) around the COVID-19 outbreak. Using the TVP-VAR connectedness approach, the results show that the dynamic total connectedness across the five assets was moderate and quite stable until early 2020. After that, the total connectedness spikes and the structure of the network of connectedness alters, which concurs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
205
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 445 publications
(237 citation statements)
references
References 52 publications
28
205
1
3
Order By: Relevance
“…Our work is closely related to recent research on the effects of COVID-19 within the literature on economics and finance. Notably, it nicely complements the growing literature on the effects of COVID-19 on financial markets (e.g., Alola et al 2020 ; Aloui et al 2020 ; Bouri et al 2020 ; Shahzad et al 2020 ; Sharif et al 2020 ; Gupta et al 2021 ), which has so far ignored the impact of this catastrophic event on extreme co-movements among the US equity sectors.…”
Section: Related Studiessupporting
confidence: 55%
See 1 more Smart Citation
“…Our work is closely related to recent research on the effects of COVID-19 within the literature on economics and finance. Notably, it nicely complements the growing literature on the effects of COVID-19 on financial markets (e.g., Alola et al 2020 ; Aloui et al 2020 ; Bouri et al 2020 ; Shahzad et al 2020 ; Sharif et al 2020 ; Gupta et al 2021 ), which has so far ignored the impact of this catastrophic event on extreme co-movements among the US equity sectors.…”
Section: Related Studiessupporting
confidence: 55%
“…The energy and material sectors are not driven by global risk aversion. The role of fear and uncertainty in the dynamic connectedness structure of financial markets is highlighted by recent studies (e.g., Bouri et al 2020 ; Sharif et al 2020 ; Gupta et al 2021 ) showing that the dynamics are non-linear and strongly pronounced during the COVID-19 pandemic. These recent findings also concord with evidence put forward by Hesse and Frank ( 2009 ) linking funding stress and equity markets in advanced economies during the financial crisis.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…Our study is relevant as disease outbreaks, such as the current COVID-19 pandemic, can distort economic activities, causing economic and financial uncertainties, triggering increased unemployment. These resultant consequences may lead to international financial chaos that disturbs asset allocations and risk management and, most notably, financial stability (Bouri et al, 2020). According to Qin et al (2020), the COVID-19 pandemic had a substantial negative net effect on oil prices by as much as 80%.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…However, this often-held negative assertion may change as a pandemic outbreak may trigger a negative supply shock, driving up prices (Qin et al, 2020). Therefore, a study of this nature may help investors re-stabilize their portfolios, switching from risky assets to safe-haven assets in order to mitigate portfolio risks (Bouri et al, 2020).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…The motivation for our study is threefold. First, the current COVID-19 pandemic has shown that stock markets and financial markets of many countries are sensitive to the pandemic (see, Bouri et al, 2020). Second, uncertainty that created by pandemics that impact health have significant influence on investors' actions (Baker et al, 2020) and sentiments (HaiYue et al, 2020).…”
Section: Introductionmentioning
confidence: 99%